Use of a novel 1‐hour protocol for rapid frozen section immunocytochemistry, in a case of squamous cell carcinoma treated with Mohs micrographic surgery. (1st June 2018) - Sinha, K.; Ali, F.; Orchard, G.; Rickaby, W.; Shams, M.; Mallipeddi, R.; Patalay, R.
Summary: For squamous cell carcinoma (SCC) treated using Mohs micrographic surgery (MMS), interpretation of haematoxylin and eosin‐stained frozen sections can be challenging. In these situations, ancillary use of immunostaining is a useful tool for the Mohs surgeon. However, use of immunostaining in MMS laboratories is limited, mainly because current manual immunostaining platforms are subject to operator error, and automated immunostaining, albeit accurate, is too slow for inclusion in MMS. In this report, we describe a novel 1‐hour protocol for rapid frozen section immunocytochemistry, using the pancytokeratin markers AE1/AE3. This protocol has been specifically designed to integrate the speed of manual techniques and the accuracy of automated platforms, making it a valuable addition to the MMS laboratory. We propose that in selected or histologically challenging cases, there is a role for the use of this novel protocol, allowing the Mohs surgeon to more confidently declare tumour clearance, thus preventing further unnecessary surgery and preserving healthy tissue.